A Case of Bilateral Internal Carotid Artery Complete Occlusion - Mrugal Doshi; Arti Muley; Sunil Kumar; Sukhaswarup Kanojiya (Journal of Integrated Health Sciences)
Complete bilateral intracranial internal carotid artery occlusion is a rare disease with grave prognosis. It may cause recurrent stroke and extensive disability. We discuss a case of 62-year-old man who presented with sudden onset right sided hemiplegia, and GCS 7/15. CT scan revealed acute ischemic infarct in left MCA territory with mass effect and compression over the left lateral and third ventricle. Cerebral angiography showed bilateral intracranial internal carotid artery and middle cerebral artery occlusion. We present the case in view of wide range of presentation which depends on collateral formation and lack of specific guidelines for management.